On death row ; Community power ; A trip to Shangri-La [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1994)
Deals with the imposition of death penalty with Fernando Galera as the first recipient of this punishment; people in Negros Occidental saving their environment; and Sagada Mountain Province, a haven for artist, nature lovers and adventure seekers.
On death row (13 min.) -- Community power (12 min.) -- A trip to Shangri-La (15 min.)
VHS.
Keywords: Capital punishment -- Philippines; Human ecology; Man -- Influence of environment -- Philippines; Sagada (Mountain Province).